Effects of Different Sterilization Rinses on Germination of Hemp, Cannabis Sativa, for Tissue Culture - Terry, Ash; Park, Sunghun; Motolai, Gergely; Stuart, Nathan (My University, 2022)
Hemp, Cannabis sativa, is a plant valued for its medicinal properties, fiber, and oil. While the hemp industry has grown significantly in the past years, a protocol for its tissue culture has not been publicly established. Tissue culture allows for regeneration of plants in a controlled, sterile environment while utilizing less space. Since creating a sterile environment is critical to a successful tissue culture, this study focused on the effects of different sterilization methods on contamination and germination of hemp seeds. The different sterilization rinses tested were water (control), 5% hydrogen peroxide, 70% ethanol, 20% bleach, 30% bleach, 40% bleach, and 50% bleach solutions. One of these solutions was applied to a group of hemp seeds. Within each group one third was rinsed in the solution for 5 minutes, another third for 10 minutes, and the last third for 15 minutes. The seeds were then placed onto germination media and left to germinate in a growth chamber for one week. The 20% bleach rinse for 10 minutes generated the lowest contamination rate, 4.5%, while maintaining the highest germination rate, 77.3%. Excluding the control, the 70% ethanol rinses for 5 and 10 minutes had two of the highest contamination rates and the two lowest germination rates. These results provide preliminary information about sterilization of hemp seeds for tissue culture. Once a reliable hemp tissue culture protocol is fully developed it will provide hemp growers with a dependable method to produce quality, disease free hemp.
Keywords: hemp; Cannabis sativa; seed surface sterilization; tissue culture; germination; USDA NIFA 2019-67032-29071